Limiting protease production plays a key role in the pathogenesis of the divergent clinical isolates of Staphylococcus aureus LAC and UAMS-1. Issue 1 (1st January 2021) - Rom, Joseph S.; Beenken, Karen E.; Ramirez, Aura M.; Walker, Christopher M.; Echols, Ethan J.; Smeltzer, Mark S.
ABSTRACT: Using the USA300, methicillin-resistant Staphylococcus aureus strain LAC, we previously examined the impact of regulatory mutations implicated in biofilm formation on protease production and virulence in a murine sepsis model. Here we examined the impact of these mutations in the USA200, methicillin-sensitive strain UAMS-1. Mutation of agr, mgrA, rot, sarA and sigB attenuated the virulence of UAMS-1. A common characteristic of codY, rot, sigB, and sarA mutants was increased protease production, with mutation of rot having the least impact followed by mutation of codY, sigB and sarA, respectively. Protein A was undetectable in conditioned medium from all four mutants, while extracellular nuclease was only present in the proteolytically cleaved NucA form. The abundance of high molecular weight proteins was reduced in all four mutants. Biofilm formation was reduced in codY, sarA and sigB mutants, but not in the rot mutant. Eliminating protease production partially reversed these phenotypes and enhanced biofilm formation. This was also true in LAC codY, rot, sarA and sigB mutants. Eliminating protease production enhanced the virulence of LAC and UAMS-1 sarA, sigB and rot mutants in a murine sepsis model but did not significantly impact the virulence of the codY mutant in either strain. Nevertheless, these results demonstrate that repressing protease production plays an important role in defining critical phenotypes in diverse clinical isolates of S. aureus and that Rot, SigB and SarA play critical roles in this regard.